The Mediating Role of Communication in Fostering Religious Tolerance within a Diverse Society - Abadi, Totok Wahyu; Zetira, Andrea Resha; Balahmar, Ahmad Riyadh Umar; Longani, Kirti Dang (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to examine the influence of social prejudice, local wisdom, social piety, religious identity, and communication behaviour on religious tolerance in Sidoarjo Regency. It focuses on the mediating role of communication behaviour in strengthening or weakening the impact of these variables on religious tolerance. A quantitative research approach was adopted, using a structured questionnaire to collect data from respondents in the Sidoarjo Regency. The data was analysed using Structural Equation Modelling (SEM) to test the relationships between the variables and the mediating role of communication behaviour. The results show that communication behaviour plays a crucial role in mediating the influence of social prejudice, local wisdom, social piety, and religious identity on religious tolerance. While social prejudice, local wisdom, and religious identity do not have direct significant effects on tolerance, their impact is enhanced through effective communication. Communication behaviour, characterised by openness, empathy, and support, positively influences religious tolerance, whereas ineffective communication diminishes the positive effects of other variables. The findings suggest that strategies to improve religious tolerance should prioritise communication behaviour. Policymakers, educators, and community leaders are encouraged to implement programmes that foster open dialogue, empathy, and respect among diverse religious groups to strengthen social harmony. This study provides new insights into the role of communication behaviour as a mediating variable in the relationship between social factors and religious tolerance, offering practical implications for enhancing tolerance in multicultural societies.